Factors Influencing Student Achievement: A Systematic Review - Suhaini, Mazlili; Ahmad, Adnan; Hawa Harith, Siti (International Journal of Psychosocial Rehabilitation, 2020)
The achievement of students is regarded as a crucial indicator of excellent academic performance. This study mainly focuses on investigating the influences of teacher, student, school, and family factors on students’ achievement. Few systematic reviews were made on the absolute factors that influence their achievement. Under the management of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement review technique, a systematic review of the Scopus and Web of Science databases identified 10 related studies. Further review of these articles led to four main themes related to students’ achievement, namely teacher, student, school, and family. Subsequently, a total of 11 sub-themes were further generated by these four themes. Several highlighted recommendations presented specific and standard systematic reviews for each theme, and thorough qualitative focus was placed on the negative impacts of each factor. This study also aims to further investigate the influence of the gender factor on students’ achievement.